TIPOLOGI MODERN DALAM METODOLOGI AHLI HADIS - Nur Hamidah Pulungan (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2022)
This research, which is a literature review, discusses several standards of understanding Hadith formed by experts in Islamic studies with a well-known textual and contextual basis known as the methodology of hadith experts. The research includes the definition of the methodology of hadith experts, techniques and processes for developing understanding of hadith, as well as an overview of modern methodologies that are currently developing. Modern typologies in understanding hadith in particular include the orientalist method, the rational method, the method of the salaf hadith experts and the moderate method.